Case Report: A Preferred Reconstructing Modality to Restore Neoplastic Nasal Alar Subunit Defects: Sequential Facial Artery Perforator Flaps - Wu, Bihua; Yang, Sanhong; Li, Hai; Zhang, Tianhua; Xiao, Shune; Wei, Zairong; Deng, Chengliang (Frontiers in Surgery, 2022)
Background: Achieving perfect repair of a nasal defect with the recovery of cosmetic subunits has become a challenge to plastic, dermatologic, and head and neck surgeons. The study aimed to evaluate the effect of reconstructing neoplastic nasal alar subunit defects with sequential facial artery perforator flaps produced from nasolabial groove tissue. Methods: A retrospective analysis of 20 patients who had undergone reconstruction for neoplastic nasal alar defects with this technique from January 2017 to October 2019 was performed. The reconstruction procedure used sequential facial artery perforator flaps. The surgical procedure used and follow-up results achieved have been documented photographically for all patients. Results: The aesthetic and functional results of surgery were satisfactory in all the 20 patients. After all surgeries, the reconstructed alar tissues were compliant, bilateral symmetries of the alae and nasolabial grooves were satisfactory, and no patients exhibited color mismatches between the flaps and surrounding tissues. During a mean follow-up period of 22 months, none of the patients exhibited alar retraction, inferior displacement, deformation, or hypertrophic scarring. Conclusions: The sequential facial artery perforator flap technique created with nasolabial groove tissue to reconstruct neoplastic nasal alar defects is a simple single-stage procedure that provides excellent surgical outcomes.